THE LIFE QUALITY OF COMMERCIAL SEX WORKERS FROM A CITY IN PORTO ALEGRE'S METROPOLITAN REGION (Fiep Bulletin - online, 2014)
The research group Body, Movement and Health, of the Feevale University Center, through the research line of Health Training, seeks to understand minority groups of our society and their lifestyles, including the life quality. Therefore, this research aimed to verify the components of the lifestyle of commercial sex workers from a city in Porto Alegre's metropolitan region. The methodology used was quantitative paradigm, with cross design and consecutive sample, and a semi-structured questionnaire. The data analysis was done through simple statistical and data analyzed followed the model of the “Pentáculo do Bem-Estar”. Mean age was 26.4 years; 35.9% of the sex workers had not completed the fundamental education and; 28.2% have a stable relationship. 46.2% do not practice physical activity; 23.1% responded that always feel stressed, being irritation the most cited symptom of stress (84.2%). 79.5% have already been HIV-tested; 84.6% of the interviewees reported that always use condoms with their clients. 47% are outside the range considered normal for BMI. The results indicated the need for educational activities, mainly on the nutritional components; habits of physical activity and; on preventive measures with information on the harmful effects of smoking; alcohol and drugs consumption and; the importance of the condom use in all sexual relations.
Keywords: Commercial sex workers; Life quality; Lifestyle